2015
DOI: 10.1186/s12936-015-0619-1
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmodium vivax rhoptry neck protein 5 is expressed in the apical pole of Plasmodium vivax VCG-1 strain schizonts and binds to human reticulocytes

Abstract: BackgroundDifferent proteins derived from the membrane or the apical organelles become involved in malarial parasite invasion of host cells. Among these, the rhoptry neck proteins (RONs) interact with a protein component of the micronemes to enable the formation of a strong bond which is crucial for the parasite’s successful invasion. The present study was aimed at identifying and characterizing the RON5 protein in Plasmodium vivax and evaluating its ability to bind to reticulocytes.MethodsTaking the Plasmodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 59 publications
1
25
0
4
Order By: Relevance
“…It cannot be ruled out that proteins must first interact with proteins on host cell membrane for this to occur, as seen in this Pv RON4 study (Figure ). It has been found that one Pv RON5 region and some Pf RON5 20 residue‐long peptides specifically interact with RBC membrane (Arevalo‐Pinzon et al, ; Curtidor et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It cannot be ruled out that proteins must first interact with proteins on host cell membrane for this to occur, as seen in this Pv RON4 study (Figure ). It has been found that one Pv RON5 region and some Pf RON5 20 residue‐long peptides specifically interact with RBC membrane (Arevalo‐Pinzon et al, ; Curtidor et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Using P. vivax strains adapted in non‐human primates (Pico de Coana et al, ) or infected patients' blood (Bozdech et al, ) has enabled comparative approaches with other Plasmodium species (Patarroyo, Calderon, & Moreno‐Perez, ) or using omic sciences (Moreno‐Perez, Degano, Ibarrola, Muro, & Patarroyo, ; Venkatesh et al, ) to identify a significant amount of proteins expressed in P. vivax schizonts (Sch) and Mz (Patarroyo et al, ). Pv RON2 (Arevalo‐Pinzon, Curtidor, Patino, & Patarroyo, ), Pv RON4 (Arevalo‐Pinzon, Curtidor, Abril, & Patarroyo, ), and Pv RON5 (Arevalo‐Pinzon, Bermudez, Curtidor, & Patarroyo, ) have been identified recently; these are homologous to those identified in P. falciparum , which are located in the apical extreme of P. vivax Colombia Guaviare 1 (VCG‐1) strain Sch. Different biochemical techniques have been used to report a conserved Pv RON5 fragment located towards the carboxyl‐terminal extreme interacting with RBC, having a preference for CD71 + cells (Arevalo‐Pinzon et al, ), suggesting that RONs could be participating in host–parasite interactions, similar to that found in P. falciparum .…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations